2000
DOI: 10.1177/106591290005300204
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Context and Contact Effects on Racial Attitudes

Abstract: The inter-group contact hypothesis states that intera ctions between individuals belonging to different groups will influence the attitudes and behavior between members of these different groups. The two dominant measures of inter-group contact are context (i.e., size of a minority group within a specified geographic area) and individual behavior (i.e., personal contact between members of the majority and minority groups). The contextual and behavioral measures of contact produce divergent finings. The context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(56 citation statements)
references
References 20 publications
1
55
0
Order By: Relevance
“…As already mentioned, conflict theory predicts anti-immigration attitudes to increase with immigrant group size, while contact theory expects diversity to promote familiarity and tolerance (Stein et al 2000;Schlueter and Scheepers 2010). We test these theories by including in the models the percentage of immigrants over the whole population; and the percentages of immigrants born within and outside the EU to account for regional diversity in inter-group contact.…”
Section: Regional Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…As already mentioned, conflict theory predicts anti-immigration attitudes to increase with immigrant group size, while contact theory expects diversity to promote familiarity and tolerance (Stein et al 2000;Schlueter and Scheepers 2010). We test these theories by including in the models the percentage of immigrants over the whole population; and the percentages of immigrants born within and outside the EU to account for regional diversity in inter-group contact.…”
Section: Regional Characteristicsmentioning
confidence: 99%
“…According to both theories, two basic aggregate sources of threat should be included in the model: the economic circumstances of the area and the size of the minority group relative to the native population (Stein et al 2000). While intergroup contact theory predicts that higher concentrations of immigrants and exposure to an ethnically diverse environment will foster more positive feelings between the two groups (Marschall and Stolle 2004), intergroup conflict theory predicts the opposite effect.…”
Section: Empirical Findings: the Local Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bledsoe et al (1995) found that African Americans who lived in more racially diverse neighborhoods developed lower levels of group solidarity and stronger attachments to whites and other groups in society. Other work has found that whites who live in closer proximity to African Americans and other minority groups experience increasing racial hostility and prejudice (Fosset and Kielcolt, 1989;Giles, 1977;Giles and Hertz, 1994;Glaser, 1994;Key, 1949;Stein et al, 2000;Taylor, 1998;Wright, 1997). However, as Oliver and Mendelberg (2000, p. 575) point out, the impact of racial threat on whites' racial attitudes has typically been demonstrated with bivariate analyses so that the effects of other salient contextual features are infrequently controlled.…”
Section: Neighborhoods As Settings For Social Interaction and The Devmentioning
confidence: 99%
“…Indeed, there is a well-established link between neighborhood social organization, including neighborhood racial composition, and a broad range of psychological orientations such as alienation, anxiety, fear, suspicion of out-groups, and mistrust (see e.g., Oliver and Mendelberg, 2000). However, this work tends to focus on either the relationship between racial context and racial attitudes (Bledsoe et al, 1995;Ellison and Powers, 1994;Sigelman and Welch, 1993;Stein et al, 2000) or neighborhood social organization and more general attitudes like trust (Massey, 1996;Ross et al, 2001)-but not both. Moreover, very rarely have researchers measured the extent or nature of social interactions occurring within neighborhoods or considered the possibility that social interaction might counter the negative effects of living in racially or socio-economically heterogeneous places.…”
mentioning
confidence: 99%